DEVELOPMENT OF SHARED-TYPE INTEGRATED SCIENCE E-MODULE BASED ON ETHNOSCIENCE ON THE TOPIC OF HUMAN EXCRETORY SYSTEM - Azmi, Neli; Sari, Monica Prima (Universe, 2024)
This research is motivated by the limited availability of integrated science teaching materials according to the demands of the 2013 curriculum and learning is not yet based on ethnoscience. This study aims to develop an ethnoscience-based integrated science e-module on the topic of human excretory system that is valid and practical. This type of research is Research and Development (R&D) using a-4D model with four stages, namely: define, design, develop and disseminate. The validity and practicality test instruments were in the form of a questionnaire with product validators from three science education lecturers, while the practicality test was carried out by 2 science teachers and 26 junior high school students in class VIII. The data analysis technique used descriptive statistical analysis. Based on the data analysis, the validity and practicality of the product were obtained with an average validity of 87.36 with a very valid category. The average value of the practice of using integrated science e-modules according to teachers and students is 92.96 and 86.89, each in the very practical category. So it can be concluded that the shared-type integrated science e-module based on ethnoscience on the human excretory system material is valid and practical to use.